The other side of the badge: police as victims of violence - Hine, Kelly (Violence and victims, 2025)
When considering police within violence and victims research, the emphasis typically falls on the police as responders to victims; however, little research has explored the perspective of police officers as victims of violence themselves. Through a systematic literature review of contemporary assaults toward police, 11 empirical articles were identified and analyzed with four main themes emerging: the retaliatory nature of police-citizen dynamics, specific predictors of police assaults, environmental features of assaults, and the impact of assaults. These findings provide evidence-based insights, identify research gaps, and help guide future research agendas, ultimately providing a foundational resource for policymakers, law enforcement agencies, and researchers in developing targeted interventions and policies to enhance officers’ safety, foster positive police-community relations, and promote a safer and more resilient society.